Experimental study on ammonia/hydrogen/air combustion in spark ignition engine conditions. (1st June 2020) - Lhuillier, Charles; Brequigny, Pierre; Contino, Francesco; Mounaïm-Rousselle, Christine
Highlights: NH3 fueling of a modern SI engine was very successful in terms of performance. Hydrogen blending results in ignition and flame propagation benefits. Hydrogen blending should be kept low to maximize the indicated efficiency. The laminar burning velocity describes well the propagation of the flame. High unburned NH3 and NOx emissions need to be mitigated by appropriate techniques. Abstract: The mitigation of climate change requires the increasing use of variable renewable energy sources. Energy storage and transport solutions will contribute to ensure the stability, reliability, and flexibility of the energy systems in that context. Ammonia is a well-known chemical of formula NH3 and, amongst other electrofuels, a promising energy carrier and carbon-free combustible fuel. In the present experimental study, engine performance, combustion characteristics and pollutant emissions of a recent spark ignition engine fueled with premixed ammonia/hydrogen/air mixtures were assessed. Gaseous ammonia blends in a wide range of hydrogen fuel fractions and equivalence ratios were tested at two different engine loads. Results show performances comparable with conventional fuel operation when the appropriate promotion strategies are used. Specifically, blending up to 20% hydrogen in the fuel by volume improves the cyclic stability and avoids misfires, while granting the best work output and indicated efficiencies near stoichiometry. Higher hydrogen fractions result in depleted efficiency, attributed to higher wall heat losses. The combustion duration is directly correlated to the LBV of the mixtures, thus being accelerated by hydrogen blending. The accelerating effect of hydrogen is particularly remarkable during the initial stage of the combustion. Hydrogen appears therefore mainly as an ignition promoter. Increasing the engine load improves the furnished work and allows to extend the operating boundaries in terms of mixture composition.